Epigenetic and Neurodevelopmental Perspectives on Variation in Parenting Behavior - Jensen, Catherine L. (2012)
Mother-infant interactions in rodents can be used to explore the biological basis of postnatal parental effects. There is emerging evidence from laboratory studies that variation in early life experiences can induce molecular changes in the developing brain which lead to activation or silencing of genes. These epigenetic effects may account for the stability of the effects of parenting on offspring development and the transmission of parenting from one generation to the next. In this article, we highlight evidence supporting a role for epigenetic mechanisms in the consequences, transmission, and variability in parenting. Although primarily drawn from laboratory studies in rodents, this evidence may also provide some insights into key questions within the study and practice of human parenting. We discuss these questions, highlighting both the challenges and benefits of using translational approaches.